Legal Protection of Pilgrims on Health Istithaah Standards in Indonesia - Arsita Rasmi; Mohammad Jamin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Hajj pilgrims are obliged to carry out their worship in accordance with the provisions of Islamic law, for this reason it is necessary to carry out health checks and health guidance for Hajj pilgrims in the concept of regulating Hajj health istithaah, namely Minister of Health Regulation Number 15 of 2016. Learn from the implementation of the Hajj in 2023 where the death rate for Hajj pilgrims is high , the government is drafting new regulations strengthening standards for determining Hajj health istithaah. This research is normative legal research and is descriptive analytical in nature. The results of the research show that this new regulation does not fulfill the aspect of legal protection for Hajj pilgrims because some of the Hajj pilgrims who are determined to not meet the Hajj health istithaah requirements while not having enough time to improve their health conditions in order to achieve istithaah. Specific and intensive health guidance is needed to prepare the Hajj pilgrims' health istithaah.